Fig. 6 in Tissue-specific localization of polyketide synthase and other associated genes in the lichen, Cladonia rangiferina, using laser microdissection - Elshobary, Mostafa E.; Becker, Michael G.; Kalichuk, Jenna L.; Chan, Ainsley C.; Belmonte, Mark F.; Piercey-Normore, Michele D. (Zenodo, 2018)
Fig. 6. Biosynthetic pathway showing the putative conversion of fumarprotocetraric acid from atranorin according to de Armas et al. (2016). Published as part of Elshobary, Mostafa E., Becker, Michael G., Kalichuk, Jenna L., Chan, Ainsley C., Belmonte, Mark F. & Piercey-Normore, Michele D., 2018, Tissue-specific localization of polyketide synthase and other associated genes in the lichen, Cladonia rangiferina, using laser microdissection, pp. 142-150 in Phytochemistry 156 on page 147, DOI:10.1016/j.phytochem.2018.09.011, http://zenodo.org/record/10484507